Cover Feature: The ARTISTIC Online Calculator: Exploring the Impact of Lithium‐Ion Battery Electrode Manufacturing Parameters Interactively Through Your Browser (Batteries & Supercaps 3/2022). Issue 3 (11th February 2022) - Lombardo, Teo; Caro, Fernando; Ngandjong, Alain C.; Hoock, Jean‐Baptiste; Duquesnoy, Marc; Delepine, Jean Charles; Ponchelet, Adrien; Doison, Sylvain; Franco, Alejandro A.
Abstract : The Cover Feature illustrates an operator using the ARTISTIC Online Calculator from a tablet and running the associated 3D‐resolved physics‐based models in HPC facilities to predict the impact of manufacturing parameters on the microstructure of a lithium‐ion battery electrode. More information can be found in the Concept by A. A. Franco and co‐workers .